2021
DOI: 10.1097/psy.0000000000000951
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Overperception of Airflow Obstruction in Older Adults With Asthma

Abstract: Objective: Older adults are at increased risk for depression and poor asthma outcomes. We examined whether depressive symptoms are associated with overperception of airflow obstruction and a pattern of worse asthma control, but not pulmonary function. Methods: We recruited a cohort of adults with asthma 60 years and older in East Harlem and the Bronx, New York. Baseline measures included the Geriatric Depression Scale, Asthma Control Questionnaire, and Mini Asthma Quality of Life Questionnaire. Spirometry was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Depressive symptoms have been found to influence how individuals perceive, process, and attend to information, with them often focusing on the negative aspects of a situation ( 43 – 45 ). Therefore, adolescents with asthma and comorbid depressive symptoms may perceive more asthma symptoms than their counterparts without depressive symptoms, resulting in their overreporting of symptoms ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms have been found to influence how individuals perceive, process, and attend to information, with them often focusing on the negative aspects of a situation ( 43 – 45 ). Therefore, adolescents with asthma and comorbid depressive symptoms may perceive more asthma symptoms than their counterparts without depressive symptoms, resulting in their overreporting of symptoms ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mechanisms by which depression may induce asthma include central and autonomic nervous systems' actions, and depression is associated with autonomic dysregulation in the form of cholinergic activation, leading to airway constriction [20]. This hypothesis [25][26][27] can explain the mechanism by which depression causes or increases asthma. Previous research [12,13,20,22] and this study showed that depression affects asthma.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a pilot trial with 53 participants 60 years or older with a physician diagnosis of asthma from hospital-based clinics in the Bronx and East Harlem, New York. Participants with underperception of airflow obstruction 25% of the time or higher were recruited from a longitudinal, observational study ( see parent study [ 7 ]). Participants who spoke English or Spanish and were prescribed an asthma controller medication were eligible.…”
Section: Methodsmentioning
confidence: 99%